Pengaruh Audit Capacity Stress, Komite Audit Dan Audit Report Lag Terhadap Kualitas Audit - Putri Wardah Mar’atus Izzah; Syamsuri Syamsuri (CV. ITTC INDONESIA, 2025)
This study was conducted to examine and obtain empirical evidence of the influence of Audit Capacity Stress, Audit Committee and Audit Report Lag on Audit Quality. This study was conducted on Banking subsector companies listed on the Indonesia Stock Exchange (IDX) in 2019 - 2024. The methodology used in this study is logistic regression because the dependent variable of this study is a dummy. And for sample selection, it was carried out using a purposive sampling method from secondary data in the form of annual reports and found 32 sample companies where the number of observations was 6 years, so that the total sample in this study was 192 annual reports. Testing was carried out using software assistance, namely eviews 13. Based on the results of the study, partially, it shows that simultaneously, it shows that Audit Capacity Stress, Audit Committee and Audit Report Lag have an effect on Audit Quality. Partially, Audit Capacity Stress, Audit Committee have no effect on Audit Quality, while Audit Report Lag partially has a negative effect on Audit Quality. This indicates that the slower the auditor performs the audit and the later the audit report is signed, the greater the audit report lag, which indicates a decline in audit quality. A shorter audit report lag indicates improved and better audit quality.